Driving Excellence through Person-Organization Fit: How Organizational Culture and Job Satisfaction Shape Employee Performance at Hotel & Convention in Cirebon - Adam Tegar Alam; Damar Adanan Setiawan; Muhamad Alwi (Management Analysis Journal, 2025)
The aim of this research is to re-examine the relationship between organizational culture and employee performance through job satisfaction as a mediating variable. The hospitality industry in Indonesia, with its significant contribution to the economy, faces challenges in improving hotel performance, particularly reflected in the decline in revenue, as experienced by Hotel & Convention XYZ in Cirebon. This study also attempts to use the Person-Organization Fit (P-O Fit) theory as the theoretical foundation to analyze the relationships among the research variables. This study employs a quantitative-explanatory approach with a census sampling technique, involving 166 employees of Hotel & Convention XYZ in Cirebon who have worked for more than one year. Data was collected through a Likert scale 1-5 based questionnaire. The collected data was then analyzed using the SEM-PLS analysis method through the SmartPLS 4 application. The results of the study indicate that an organizational culture that is well internalized can improve overall employee performance. The study also shows that job satisfaction plays a partial mediating role, making it a potential strategic alternative for companies to improve employee performance, particularly in the hospitality industry.